Blockchain-Enabled Decentralized Trust Management and Secure Voting system - Reddaiah, Somisetty; Subramanyam, Ramanabaoyina; Refonaa, J.; Jany Shabu, S. L.; Maheswari; Praveen, S. (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
Blockchain technology has seen a huge increase in popularity as a result of its ability to provide a transparent and decentralized platform for numerous applications. In order to solve the inadequacies of existing systems, a decentralized trust management and voting system that makes use of blockchain technology is proposed. The system uses the benefits of decentralization, transparency, and immutability of blockchain technology to ensure the security and integrity of voting and trust data. By employing smart contracts, the system automates the verification process and eliminates the need for middlemen, which reduces costs and improves efficiency. Decentralized consensus methods are also a part of the system, enabling reliable and impartial voting processes. The use of encryption safeguards the privacy and secrecy of the participants. The suggested system has the potential to revolutionize voting and trust management because it offers a secure and reliable environment.